Serum vitamin D levels in Berliners of Turkish descent -a cross-sectional study - Lilian Krist; Theresa Keller; Heiko Becher; Karl-Heinz Jöckel; Martin Schlaud; Stefan N. Willich; Thomas Keil (BMC, 2019)
Abstract Background Vitamin D levels may differ between migrant and non-migrant populations, especially among non-western immigrants living in a country with limited sun exposure such as Germany. This study examined serum vitamin D concentration and associated factors among Berliners with and without Turkish background. Methods Two samples (with and without Turkish roots) were recruited in the inner city of Berlin for a cross-sectional study assessing serum vitamin D concentration. Linear regression analyses were used to examine sociodemographic, lifestyle and medical factors associated with serum vitamin D levels. Results In the analyses, we included 537 subjects (39% men and 61% women, age 43.2 ± 12.5 (mean ± standard deviation) years) with and 112 without Turkish background (46% men and 54% women, age 46.7 ± 14.6 years). The Turkish sample had lower mean (95%-Confidence Interval) vitamin D levels than the non-Turkish sample: 22.7 nmol/L (21.5;23.9) vs 34.7 nmol/L (31.9;37.5), p < 0.001. In the Turkish female subgroup, veiled women had considerably lower levels than unveiled women: 14.4 nmol/L (11.5;17.3) vs 24.9 nmol/L (23.1;26.7), p < 0.001. Multivariable regression analysis revealed that among the Berliners of Turkish descent, being active less than 150 min per day, and being overweight/obese were independently associated with a lower vitamin D concentration. In the non-migrant sample besides being overweight and obese, female sex was associated with lower vitamin D concentrations. Conclusions Serum vitamin D levels were considerably low in Berliners of Turkish descent, and especially in veiled women. Potentially modifiable factors of low vitamin D levels were high BMI and low physical activity. These findings should be considered in the development of future public health strategies for subpopulations with Turkish migration background.